TEAjudo - plataforma online de apoio para professores com alunos autistas em sala de aula - Adolfo, Gisele Lauxen (2024)
The production of knowledge fostered within a research group in schools can help change pedagogical practices, serving as an indication for the design of new training models that can be used in the future by all educators. In this sense, the research aims to develop an online platform with a view to collaborating in the actions and planning of teachers when students with autism spectrum disorder are included in the regular education network. This research will take place in formal teaching environments, therefore it will be qualitative, as it privileges the context, focusing on the whole, not as a fragmented section, disconnected from the totality in which it moves or is constructed. As for its objectives, it will have an exploratory character, as it will seek to analyze the variables within the process of inclusion of autistic students, providing an overview of this reality, with a view to improving the quality of the education provided to them. In terms of methods, it is classified as multimethod. The “TEAjudo” study platform will be an element that can help inclusion, as it will provide the necessary support for the teacher, generating beneficial impacts on society as a whole, as it will contribute to the educational equity of students, whether they are neurotypical or autistic. By using this platform, the teacher will be provided with scientific studies free of charge, training in practice and thus being able to work with quality and safety on inclusion, guaranteeing learning for everyone. It is important to make it clear that, according to the results of this research, it is clear that teachers do not know much about Autism Spectrum Disorder and feel unprepared to work with inclusion, demonstrating the need for help structuring teaching practices and curricular adjustments. The platform was evaluated through a case study, by 5 Basic Education teachers from the municipal education network of Quinze de Novembro/RS, who evaluated the platform in terms of ease, usefulness and difficulties encountered. All were unanimous in affirming positivity on the three issues, generating great assertiveness so that educators who have students with ASD enrolled in the regular education network can use the TEAjudo Platform as an ally in planning their classes.